A western world - DeForge, Michael, 1987- (Koyama Press, 2018)
"Short, succinct and, more often than not, strange stories have always been a central part of Michael DeForge's oeuvre. In a career that's volume outweighs its years, DeForge's most powerful work has often been his most pithy."--Amazon.com.